RANCANG BANGUN SISTEM INFORMASI GEOGRAFIS DAN PEMESANAN LAPANGAN BULU TANGKIS DI KOTA BATAM - Zebua, Oswald Motani; Amrizal, Amrizal (LPPM Universitas Putera Batam, 2023)
In Indonesia, badminton is one of the most popular sports among the people, where every competition on the world stage, Indonesian people flock to watch every match and it is not uncommon for athletes from Indonesia to win in every competition. In the era of the development of information technology, especially information systems, there are still many badminton courts that still use field reservations using the manual method by taking notes on paper, ordering by telephone or WA, and so on. This can pose a risk of loss of ordering data during the recording process. For this reason, this research creates a web-based application to solve the problem of renting a badminton court in Batam City. This web-based application is created using the extreme programming method with the PHP and HTML programming languages. The purpose of this research is to make it easier for tenants to make bookings on badminton courts and make it easier for managers to collect data by utilizing the existing internet network.